2019
DOI: 10.1038/s41598-019-45377-8
|View full text |Cite
|
Sign up to set email alerts
|

CD56 expression in breast cancer induces sensitivity to natural killer-mediated cytotoxicity by enhancing the formation of cytotoxic immunological synapse

Abstract: We examined the potential value of the natural killer (NK) cell line; NK-92, as immunotherapy tool for breast cancer (BC) treatment and searched for biomarker(s) of sensitivity to NK-92-mediated cytotoxicity. The cytotoxic activity of NK-92 cells towards one breast precancerous and nine BC cell lines was analyzed using calcein-AM and degranulation assays. The molecules associated with NK-92-responsiveness were determined by differential gene expression analysis using RNA-sequencing and validated by RT-PCR, imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 64 publications
0
26
0
Order By: Relevance
“…Previous reports on the role of CD56 in NK cell lytic function have focused on homotypic interactions between CD56 on NK cells and target cells and have led to conflicting conclusions about the role that CD56 plays in cytotoxicity (4,(30)(31)(32). To test the cytotoxic function of wild-type (WT) and CD56-knockout (KO) cell lines against CD56-negative target cells, we performed 51 Cr-release cytotoxicity assays.…”
Section: Cd56-ko Nk Cells Have Impaired Lytic Function Towards Cd56-nmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports on the role of CD56 in NK cell lytic function have focused on homotypic interactions between CD56 on NK cells and target cells and have led to conflicting conclusions about the role that CD56 plays in cytotoxicity (4,(30)(31)(32). To test the cytotoxic function of wild-type (WT) and CD56-knockout (KO) cell lines against CD56-negative target cells, we performed 51 Cr-release cytotoxicity assays.…”
Section: Cd56-ko Nk Cells Have Impaired Lytic Function Towards Cd56-nmentioning
confidence: 99%
“…Previous studies have demonstrated that CD56 can promote human NK cell cytotoxic function against some CD56 + target cells (29)(30)(31)(32), although in some cases lysis is not enhanced by target cell CD56 expression (4). As these studies focused on homotypic CD56-mediated interactions, the significance of CD56 binding to heterotypic ligands is unclear yet is likely relevant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…aberrantly expressed CD56, also known as neural cell adhesion molecule-1 (NCAM-1). Aberrant CD56 expression is a common finding for rhabdomyosarcoma, including ARMS [26], and a recent study indicates an association between tumor-cell expression of CD56 and sensitivity to NK-cellmediated killing in breast cancer [27].…”
Section: Discussionmentioning
confidence: 98%
“…Toll-like receptor-activated plasma-like dendritic cells inhibited growth of BC cells (48). CD56 enhanced formation of cytotoxic immune synapses and strengthened sensitivity of cytotoxicity mediated by natural killer cells (49). CD4 and CD8 T cell tumor infiltration driven by HER2-dendritic cells improved survival of BC mice (50).…”
Section: Discussionmentioning
confidence: 99%